Governance of the circular economy: a comparative examination of the use of standards by China and the United Kingdom - Flynn, Andrew; Hacking, Nick; Xie, Linjun (Elsevier, 2019)
Wastes, like other materials, have become increasingly global in their flows. The circular economy (CE) is a multi-level sustainability transition linked to the global trade in waste. China has long been a key trading partner for the West’s waste materials. However, its rethinking of the quality of traded recyclable materials has triggered a crisis in the global governance of waste flows. We utilise a Sociology of Knowledge approach to undertake comparative work to better understand how different governance arrangements may facilitate or constrain the unfolding of a CE transition. The UK and China were selected as models of liberal and authoritarian environmental governance respectively. A mixed-method approach was pursued using qualitative interviews with key stakeholders and analysis of quantitative and qualitative data from secondary sources. Thematic analysis is organised around: perceptions of the circular economy, meanings of standards, and perspectives on trade and materials.